Economic burden of stroke across Europe: a population-based cost analysis - Luengo-Fernandez, R; Violato, M; Candio, P; Leal, J (SAGE Publications, 2019)
Introduction: In 2017, 1.5 million people were diagnosed with stroke, 9 million were living with stroke and 0.4 million died because of stroke in 32 European countries. We estimate the economic burden of stroke across these countries in 2017.